Mathematics
Milenamorawska
2021-09-15 04:28:51
the answer to y=x+6 y=-2x
ANSWERS
diva0551
2021-09-15 05:28:28

y=x+6 y = -2x Plug the 2nd into the 1st equation. y=x+6 -2x = x+6 Subtract x from both sides: -2x-x=6 Simplify: -3x = 6 Solve: x = -2 Plug into the first equation: y=x+6 y=-2+6 y=4 Verify by putting both into each equation. y=x+6 y = -2x 4=(-2)+6? True 4 = -2(-2)? True x=-2, y=4

rkeitt17
2021-09-15 05:29:43

y=-2x y=x+6 subsiutte -2x=y=x+6 -2x=x+6 subtract x from both sides -3x=6 multiply -1 3x=-6 diivde 3 x=-2 subsiutte y=-2(-2) y=4 x=-2 y=4 in (x,y ) format (-2,4) is the answer

ADD ANSWER